Transformational Leadership Strategies for the Development of Preschool Educational Diversifying Modes in The New Era of Socialism with Chinese Characteristics - Liang, Fubao; Kunarak, Pragob; Viseshsiri, Pongsin (Scholar: Human Sciences, 2021)
The purpose of this research was to develop transformational leadership strategies for the development of preschool educational diversifying modes in a new era of socialism with Chinese characteristics. Opinionnaire was developed to collect data from 468 respondents through the stratified selected sampling design covering 254 kindergartens and related offices in 11 counties, cities and districts of 11 provinces from 27 June to 5 July, 2020. The data was then analyzed by demographic statistics, means, PNI, standard deviation, SWOT analysis, Pearson’s correlation, and content analysis. Deriving from the analysis, a proposal of the transformational leadership strategies was drawn up, by which the government vigorously increase supports of technology, politics, economy, social-culture, legal and security, steadily increase education inputs in all modes of kindergartens, in terms of: enlarging caring for staff, playing full roles of vision, better creating opportunities, exploring empowerment orientation, enforcing communication, enhancing trust relationship, arousing self-confidence and constructing organization culture as well.